Performance Comparison Under Stochastic Conditions. - Kewei Wang (556371) (2025)
Error bars represent ±1 standard deviation from 45,000 Monte Carlo simulations. Percentage values indicate stochastic deviations from the deterministic baseline. Statistical significance p < 0.001 for all comparisons.